Parent Training Management of Preschool ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
Parent training (PT) and parent counseling and support (PC&S) techniques were compared in the management of a community sample of preschool 3-year-old children with attention-deficit/hyperactivity disorder (ADHD) followed in the Department of Psychology, University of Southampton, UK.